Evaluating the FRSC's "Don't Drink and Drive" Media Campaign in South-east, Nigeria: Effects on Motorists' Exposure and Compliance Levels - Ngene, Hyacinth Andrew; Ifeanyi Anorue, Luke (Transactions on Transport Sciences, 2021)
Background Several campaigns on road traffic accidents have been launched by the Federal Road Safety Corps (FRSC) of Nigeria in collaboration with the Beer Sectoral Group (BSG). One such campaign is the "Don't Drink and Drive" intervention launched in 2008. This intervention was initiated to discourage drunk-driving and to improve safety on Nigerian roads through awareness creation. While it is a fact that the the combined enforcement and public education roles of the stakeholders has enormous potentials to tackle drunk driving problems, indigenous empirical evaluation on drivers' exposure and compliance to such DDD messages is scanty. This paper therefore examined motorists' exposure to FRSC's "Don't Drink and Drive" media campaign in South-east, Nigeria and its effects on their compliance levels. Methods A descriptive survey was used to elicit information from 360 registered commercial and private drivers in three selected states (Anambra, Ebonyi and Enugu) in South-eastern region of Nigeria. A multistage sampling approach was adopted in the study. Specifically, a combination of simple random sampling techniques and a purposive sampling procedure was adopted to access respondents across the region under study. Participants volunteered to complete paper version of the questionnaire at their convenience. An independent-samples t-test, a one-way between-groups analysis of variance (ANOVA) and a chi-square test for odd ratio (OR) and relative risks (RR) were performed to test the variables of interests in the study. Results Among other findings, data revealed that in terms of the participants' level of exposure to the DDD campaign, significant differences were observed in age, education, income and number of years spent driving. We also found that drivers' agreement level of the contents of the DDD campaigns was appreciable. Results particularly suggest that the DDD campaigns had a significant impact on drivers' likelihood of avoiding alcohol when driving, reducing alcohol intake at other times and educating others on the danger of drunk driving. Conclusion We conclude that the DDD campaigns might be more effective when policy designers and interventionists concerned with road safety begin to focus on the differences in the demographic characteristics of the drivers. Nonetheless, we advised that the intervention should continue alongside the use of legal back-up (i.e., by imposing some sanctions on drunk drivers) for optimal performance, while campaign efforts should factor in the roles of multiple variables that have been raised in this study.
Keywords: Impaired Driving; Nigeria; Don't Drink and Drive; Compliance; Intervention Campaign